PERCEPATAN IMPLEMENTASI E-GOVERNMENT DI KOTA BANJAR (ACCELERATION OF E-GOVERNMENT IMPLEMENTATION IN CITY OF BANJAR) - Sari, Diana (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2018)
AbstractThe implementation of e-government in West Java is already underway, several regions are considered successful, but there are still many cities/districts in West Java that still need attention, including the City of Banjar. This research was conducted to map the description of the implementation of e-government in Banjar City and the formulation of optimizations that can be encouraged to accelerate the implementation of e-government in Banjar City with an actor approach in the implementation of e-government. The research method is carried out with a qualitative approach by mapping the description from the dimensions of governance, infrastructure, and services. Forcefield analysis is carried out to encourage the strengthening of each dimension/aspect, and formulate an optimization formulation of the acceleration of e-government implementation in Banjar City. There are a number of things that can be of concern to accelerate implementation, including from the dimensions of governance, infrastructure and services by encouraging the acceleration of legal and policies related to e-government at the city level, standards, encouraging data integration, services according to main tasks and functions and inventory so and services do not overlap and ensure connectivity and interoperability of services can be appropriate.AbstrakImplementasi e-government di Jawa Barat sudah berjalan, ada beberapa daerah yang dinilai berhasil, tetapi masih banyak beberapa kota/kabupaten di Jawa Barat yang masih membutuhkan perhatian, diantaranya adalah Kota Banjar. Penelitian ini dilakukan untuk memetakan gambaran implementasi e-government di Kota Banjar serta formulasi optimasi yang dapat didorong untuk mempercepat implementasi e-government di Kota Banjar dengan pendekatan pelaku dalam implementasi e-government. Metode penelitian dilakukan dengan pendekatan kualitatif dengan memetakan gambaran implementasi dari dimensi tata kelola, infrastruktur dan layanan. Analisis force field dilakukan untuk mendorong penguatan dari masing-masing dimensi/aspek, serta merumuskan formulasi optimasi percepatan implementasi e-government di Kota Banjar. Ada beberapa hal yang dapat menjadi perhatian untuk mempercepat implementasi diantaranya dari dimensi tata kelola, infrastruktur dan layanan dengan mendorong percepatan payung hukum dan kebijakan terkait e-government di level kota, standar, mendorong integrasi data, layanan sesuai tugas pokok dan fungsi serta inventarisasi agar infrastruktur dan layanan tidak tumpang tindih serta menjamin konektivitas dan interperobilitas layanan dapat sesuai.